The Role of Notary in Binding The Security with Liability Rights - Muhammad Zaky Mushaffa (Jurnal Akta, 2020)
This research aims to determine the role of the notary in binding collateral with immovable property rights, obstacles and solutions in the implementation of binding mortgage rights and legal consequences if it is done not in front of a notary. This study uses an approach Juridical Empirical, namely legal research by approaching the existing facts by conducting research and then being reviewed and reviewed based on the relevant laws and regulations as a reference for solving problems. The result are (1) The role of a notary in binding immovable property collateral is very important, referring to article 15 paragraph (1) of the UUHT which stipulates that the Power of Attorney to Impose Mortgage Rights (SKMHT) must be made with a notary deed or deed PPAT (2) The obstacles that occur in the collateral binding process with mortgage rights can be mapped in two stages, namely the pre-binding stage, generally related to the filing of binding requirements such as the identity of the parties, the object of guarantee, and the parties' authority to act and the stage after the binding, at generally related to the attitude of the debtor and the binding process at the local National Land Agency. (3) Legal consequences of binding collateral if not carried out before a notary include the signed agreement loses its authenticity as stipulated in Article 16 paragraph (8) UUJN.